Thoraco-omphalopagus conjoined twins detected at as early as 9 weeks of gestation: Transvaginal two-dimensional ultrasound, color Doppler and fetoplacental Doppler velocity waveform findings - (:unkn) unknown (KARGER, 2006)
Here we report a case of conjoined twins that were diagnosed antenatally by routine two-dimensional transvaginal ultrasound examination at as early as the 9th week of gestational age. The fetuses were of the thoraco-omphalopagus type and were sharing the liver, as confirmed by color Doppler. There was a reversed flow in the single ductus venosus of the twins. Umbilical arterial and venous blood flow waveform did not show any abnormality for this gestational age. This case demonstrated the possibility of making an accurate diagnosis of conjoined twins in the first trimester by transvaginal two-dimensional ultrasound and color Doppler examination. Although conjoined twins were described at first trimester before, fetoplacental Doppler waveform findings at this gestational age have been described very rarely. This case demonstrated the possibility of making an accurate diagnosis of conjoined twins and delineating the extent of organ sharing in the first trimester, and early diagnosis can help the parents with the option for pregnancy termination. The importance of expert early vagi nal sonography and color Doppler findings is emphasized. Copyright (c) 2006 S. Karger AG, Basel
Keywords: conjoined twins; transvaginal two-dimensional ultrasound; color Doppler; fetoplacental Doppler; FALSE-POSITIVE DIAGNOSIS; 3-DIMENSIONAL ULTRASOUND; 1ST-TRIMESTER DIAGNOSIS; PRENATAL-DIAGNOSIS; 1ST TRIMESTER